2009
DOI: 10.1097/rhu.0b013e3181a1083d
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Dysfunction in Fibromyalgia Assessed by the Composite Autonomic Symptoms Scale (COMPASS)

Abstract: Patients with FM have multiple nonpain symptoms related to different expressions of autonomic dysfunction. There is a correlation between a questionnaire that measures FM severity (FIQ) and an autonomic dysfunction questionnaire (COMPASS). Such correlation suggests that autonomic dysfunction is inherent to FM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 7 publications
3
38
1
2
Order By: Relevance
“…Considering that there is a correlation between autonomic dysfunction and symptom severity or quality of life [11], these results may represent clinical benefits to patients who suffer from this condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that there is a correlation between autonomic dysfunction and symptom severity or quality of life [11], these results may represent clinical benefits to patients who suffer from this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic hyperactivity may also be responsible for frequent complaints of cold extremities. Interestingly, a correlation between autonomic dysfunction and symptom severity or quality of life has been previously described [11]. Heart rate variability (HRV) has been used to investigate cardiovascular autonomic modulation as a simple, sensitive, and noninvasive tool [12].…”
Section: Introductionmentioning
confidence: 99%
“…It remains to be established if the HRV differences found in this study persist in obese post-menopausal women, in men or in patients with other painful rheumatic syndromes such as rheumatoid arthritis. In this regard, it is worth noting that a previous study revealed that FM patients have significantly more autonomic symptoms (including sleeping problems) than patients with rheumatoid arthritis [26]. Even so, a pending issue is to directly compare nighttime HRV parameters in FM versus other painful rheumatic syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…[7] FMS is thought to result from ANS dysfunction initiated by a genetically impaired stress response. [8,9] ANS dysregulation of pain modulatory systems may lead to prolonged interactions among the central nervous system, the peripheral nervous system, and the immune system, such that neuroplasticity establishes a connection among the sympathetic nervous system (SNS) and nocioceptive fibers. This is postulated to result in neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%